Metamphetamine laboratories: the geography of drug production - Weisheit, Ralph A. (Western criminology review, 2010)
There has been considerable public concern and legislative activity surrounding the issue of domestic methamphetamine production. What has not been extensively examined is the broader context within which domestic methamphetamine production takes place. This study utilizes geographic location data on 14,448 seized methamphetamine laboratories to document the association between the presence of methamphetamine labs and economic factors, social factors, and crime. The study shows that laboratory seizures spiked upward immediately prior to the implementation of legislation restricting access to methamphetamine precursor drugs and declined immediately after the legislation was passed, remaining well below pre-regulation levels. However, more than a third of U.S. counties reported laboratory seizures after strict precursor regulations were in place, suggesting that while the problem of local methamphetamine lab production was diminished by precursor regulation, it was not eliminated. The study also examined factors most strongly associated with the seizure of methamphetamine laboratories at the county level. Economic instability was not a good predictor of the presence of methamphetamine labs, nor were spatial or geographic variables. In general, counties with higher lab seizure rates tended to have a predominantly White, Englishspeaking population with a substantial representation of evangelical churches. Methamphetamine laboratory counties also tended to have employment based on manufacturing, a larger farm population, single-female-headed households, a higher than average property crime rate, be more racially segregated, have a population that moved into the household within the past year, and have a higher percent of occupied housing. In sum, neither traditional measures of social disorganization nor measures of civic engagement consistently predict the presence of methamphetamine labs.